2002
DOI: 10.1080/09581590210127398
|View full text |Cite
|
Sign up to set email alerts
|

'New' genetics meets the old underclass: Findings from a study of genetic outreach services in rural Kentucky

Abstract: One of the most serious, but least examined, issues arising at the intersection of the 'new' genetics and public health is the relationship between social class and genetic burden. In the USA, concerns in ethics, policy and public discourses about genetic medicine and class structure have frequently been expressed in the notion of a potential 'genetic underclass'. The paper explores the usefulness of the genetic underclass metaphor for framing intersections of genetics and social disadvantage. Data are drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…In spite of both federal and state level legislation regarding health, rehabilitative and educational services for children with disabilities, rural resources for provision of these services are often spread thinly. While most parents in the study reported some access to occupational and other forms of therapy through early intervention programmes, access to support for their children in educational settings through the Individuals with Disabilities in Education Act (IDEA) mechanisms, and some access to Medicaid and Social Security funding for health care and income support, this access often came at considerable cost in terms of time, effort, and in some cases, family stability, particularly for mothers (see Kelly 2002). A specific analysis of parents' experiences of welfare and rehabilitative services as conditions and sources of influence on the decisions of parents is beyond the scope of this paper; the data suggest, however, that these influences are complex and cannot be considered independently of a range of contextual and demographic factors.…”
Section: Risk Control and Responsibilitymentioning
confidence: 99%
“…In spite of both federal and state level legislation regarding health, rehabilitative and educational services for children with disabilities, rural resources for provision of these services are often spread thinly. While most parents in the study reported some access to occupational and other forms of therapy through early intervention programmes, access to support for their children in educational settings through the Individuals with Disabilities in Education Act (IDEA) mechanisms, and some access to Medicaid and Social Security funding for health care and income support, this access often came at considerable cost in terms of time, effort, and in some cases, family stability, particularly for mothers (see Kelly 2002). A specific analysis of parents' experiences of welfare and rehabilitative services as conditions and sources of influence on the decisions of parents is beyond the scope of this paper; the data suggest, however, that these influences are complex and cannot be considered independently of a range of contextual and demographic factors.…”
Section: Risk Control and Responsibilitymentioning
confidence: 99%
“…B. beim Abschluss einer Krankenversicherung, was in einem Land mit überwiegend privaten Krankenversicherungen wie den USA besonders gravierende Folgen für den Einzelnen hat. Im Ergebnis würden sich also soziale und genetische Benachteiligungen gegenseitig verstärken [36]. Auch wenn der Begriff genetische Unterschicht vielleicht etwas zu drastisch gewählt ist: Die aufgeworfenen Fragen verdienen es auf jeden Fall, genauer untersucht zu werden.…”
Section: Mögliche Soziale Folgen Genetischer Testsunclassified
“…The barriers in accessing genetic services are numerous: genetics providers tend to be concentrated in urban areas or academic medical centers, the workforce is small and unevenly distributed, and insurance providers often limit coverage for genetic testing and genetic counseling (Cooksey, Forte, Benkendorf, & Blitzer, 2005; Graf, Needham, Teed, & Brown, 2013; Secretary’s Advisory Committee on Genetics Health Society, 2006; Wang, Beattie, Ponce, & Phillips, 2011). State Health Agencies (SHAs) have historically sought to mitigate some of these barriers by providing clinical services (such as genetic testing or genetic counseling) directly, contracting with healthcare providers to provide care, or sharing these responsibilities with private payers and charities (Epstein, Erickson, Hall, & Golbus, 1975; Kelly, 2002; Lessick & Townes, 1979; MacDonald, Blazer, & Weitzel, 2010; Reid et al, 1976). SHAs have myriad other responsibilities, however, and the provision of direct clinical services makes up a very small proportion of their activities.…”
Section: Introductionmentioning
confidence: 99%